Pricing in ecosystems: A generalized linear production model - Bernd Klauer (UFZ-Umweltforschungszentrum Leipzig-Halle, 1999)
In this paper a method is developed to derive prices for natural goods from information about material and energy flows within ecosystems. The derivation is based on an analogy between ecological and economic systems: both systems are characterized by flows of material and energy. To derive ecosystem prices the mathematical structure of Koopmans economic linear production model his activity analysis is applied to a material flow model of ecosystems. The ecological interpretation of these prices is discussed and the uniqueness of the price system is investigated. An algorithm for price calculation is derived and demo nstrated with a numerical example. Finally, it is discussed whether ecosystem prices may be suitable as surrogates for economic valuations of natural goods.
Keywords: Q2; 330; Price theory; evaluation of natural goods; activity analysis; general equilibrium theory; ecosystems; material flows; energy flows; Umweltökonomik; Preistheorie; Stoffstrom-Management; Aktivitätsanalyse; Allgemeines Gleichgewicht; Theorie